Da Roland blev italiener – og forelsket - Lausten, Pia Schwartz (K&K - Kultur og Klasse, 2007)
Italiensk ridderdigtning mellem epos og roman: M.M.Boiardos Orlando innamorato (1495) When Roland became an Italian – and fell in love Though marking the invention of the chivalric epic, so famously mocked by Cervantes, Boiardo’s poem Orlando Innamorato (1494) has been overshadowed by the later, more famous works of Ariosto and Tasso, and the very genre of chivalric epic tends often to be forgotten. This article describes the cultural and historical conditions for the rise of the genre in the 15th century at the Este-court of Ferrara where an elitist humanist culture paradoxically enough coexisted with a special preference among the courtiers for medieval chivalric romances. The article presents Boiardo’s poem, its many different literary sources, its socio-political functions, and its reception history. The poem borrows both from the medieval carolingian and arthurian chivalric romances, from the Greek and Latin epic, as well as from the three ‘crowns’ of the 14th century, Dante, Boccaccio and Petrarch. The article argues that it is tempting to consider the work of Boiardo an early, ‘dialogical’ novel since it presents several elements of M. Bakhtin’s definition of the genre, especially its multiplicity of different ‘voices’. But Orlando Innamorato is (just like Ariosto’s and Tasso’s epics) both too classicist and too adventure-like to be considered a modern novel. The genre Boiardo invents and represents thus reflects the complexity of the Renaissance.